Ethics and law for the health professions - Kerridge, Ian; Lowe, Michael 1960-; Stewart, Cameron 1971- (The Federation Press, 2013)
Ethics and Law for the Health Professions is a cross-disciplinary medico-legal book whose previous editions have been widely used by students, teachers and practitioners in the health professions and in law. This new 4th edition has been extensively revised and updated to take account of developments in law, biomedical science, healthcare delivery and bioethics. Sections dealing with critical reasoning, problem solving, professionalism, negligence, standards of care, public health and the emerging biosciences have been considerably expanded and entirely new chapters have been added dealing with sexuality, culture, rural health, evidence and global health